Level of food consumption score and associated factors among households in Konso Zone, Southwestern Ethiopia: a community-based cross-sectional study - Markos, Kasata; Dake, Samson Kastro; Bisetegn, Fithamlak Solomon; Nane, Debritu (Frontiers in Nutrition, 2024)
Background Despite several attempts made in the developing world to improve overall food consumption patterns, it is still a major problem. However, there is limited literature on evidence of FCS, particularly in the study area. Objective This study aimed to assess the level of food consumption score and associated factors among households in Konso Zone, Southwestern Ethiopia. Methods A community-based cross-sectional study was conducted among 488 households in Konso Zone, southern Ethiopia. Data were collected using an interviewer-administered, pre-tested, structured questionnaire. We assessed FCS through a seven-day dietary recall of food consumption. The households were labeled as “poor FCS” when they had a food composite score of <21.5; “borderline FCS” when they had a food composite score of 21.5–35; and “acceptable FCS” when they had a food composite score of >35 during the reference period. The data were entered into Epi-Data version 3.1 and exported to Statistical Package for Social Science (SPSS) version 25 for analysis. The p-value, adjusted odds ratios (AORs), and 95% confidence intervals (CIs) were used to identify the associated factors. Results The acceptable FCS among the study participants was 68.3% (95% CI: 63.9, 72.4), whereas 17.4% (95% CI: 14.1, 21.2) were borderline and 14.3% (95% CI: 11.3, 17.8) were poor. There was a higher level of acceptable FCS among households with household heads who were married (AOR = 2.22; 95% CI: 1.08, 4.58), aged 18–24 years (AOR = 0.13, 95% CI: 0.05, 0.30), farmers (AOR = 0.22, 95% CI: 0.13, 0.39), and attended formal education (AOR = 2.68, 95% CI: 1.65, 4.21). Conclusion The prevalence of acceptable FCS was found to be low. The age of the household head, marital status, occupation, and residence had a significant relationship with the study outcome. Therefore, interventions should target younger-headed and unmarried households. Policies and programs should support the ownership of farmland and promote formal education.